(untitled) (Research, Society and Development, 2023)
Child mortality is a key indicator not only for child health and wellbeing, but also for the general progress towards the Sustainable Development Goals (SDGs). Health professionals are bestowed a prominent position and must be provided with skills for fostering quality and culturally consistent healthcare. Health education practice acts as a means for optimising self-care. This is a descriptive, exploratory and transversal study with qualitative methodology, the sample of which is non probabilistic as a matter of convenience, composed of Angolan health professionals. We analysed cultural influence on Angolan maternal care of newborns and strategies for health intervention from the perspective of Angolan health professionals, as well as the performance of said professionals. Health professionals mention that cultural influence on care fosters practices which are not recommended by the WHO, with a detrimental effect on health, as happens for example in umbilical cord stump care by using products which cause omphalitis and increase the risk of sepsis and neonatal death. Said professionals defend that in view of this finding, it is fundamental to invest in strategies which will improve the quality of healthcare, in order to reduce neonatal mortality in Angola. These results support what has been described in scientific literature and studies within the same framework, reinforcing the need to pay attention to this reality.